ANALISIS ASPEK BIAS DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN ASURANSI JIWA DI INDONESIA - Benny Kurniawan (Perpustakaan Universitas Surabaya, 2017)
ABSTRACT This research aims to learn about the irrationality in Indonesian society when making purchase decision related to life insurance. This irrationality caused by the multiple aspects such as excessive optimism, representativeness bias, overconfidence, herding effect, availability, confirmation bias and framing effects. This study will describe how the life insurance purchase decisions seen from seven aspects of bias. This research is positivism basic research in quantitative and descriptive. This research data obtained by survey method where this method using questionnaires. The questionnaires was prepared and distributed to the Indonesian directly (face to face with respondents) and also indirectly (using google form). The number of samples in this study were 160 people. The data that have been collected will be analyzed based on the characteristics of the respondent. After that, the data will be measured using a Likert scale and measurement results will be tested using the validity and reliability test. Then the data will be described using descriptive statistical tests. The results of this description will be used to address the main problem of this research. Aspects of representativeness bias is not used in this study because the respondent data reliability is very low. Descriptive statistical test results from this study indicate that only availability bias and framing effects contained in life insurance purchase decision. Aspects of availability bias is a dominant aspect in life insurance purchase decision. In addition, this study also indicate that there are differences between men and women. The aspect of availability bias and framing effect occurred on men, but for women only framing bias effect occured. This study also indicate that there are difference bias result in terms of different age of respondent and the duration of life insurance ownership. Overall, this study shows that there is no bias aspect in the life insurance purchase decision. Keywords: irrationality, life insurance, excessive optimism, representativeness bias, overconfidence, herding effect, availability, confirmation bias, framing effect